Strategic management in the arts - Varbanova, Lidia; ProQuest (Firm) (New York : Routledge, 2013)
"This book looks at the unique characteristics of cultural organizations and shows readers how to tailor a strategic plan to help these organizations meet their objectives. Including examples, cases, questions and suggestions for further reading, this book is designed to accompany classes on strategic planning, cultural management or arts management"--
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Arts -- Management -- Textbooks; Strategic planning -- Textbooks; Electronic books